Flow regulation at constant head in feedwater pumps in a sugar industry - Julio R. Gómez; Vladimir Sousa; Mario S. Quintana; Percy R. Viego; Hernán Hernández; Enrique C. Quispe (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper the feasibility of energy saving by implementing flow regulation at constant load in feedwater pumps in a sugar industry is studied. As regulation strategy, the use of a variable speed drive in the hydraulic system is proposed. For the project evaluation, the Net Present Value and Payback Period techniques are used. Among the variables considered are the price of energy, the equipment useful life, financial data and those related to environmental impact. As a result, it was found that if only a commercial approach is considered, the energy saving strategy is profitable but not attractive, because investment is recovered in a period close to the useful life of technology. However, if a government focus that encourages the implementation of these energies saving strategies is considered, the investment of the project recovers in a short time.